2019
DOI: 10.1063/1.5115387
|View full text |Cite|
|
Sign up to set email alerts
|

Controlling acoustic waves using magneto-elastic Fano resonances

Abstract: We propose and analyze theoretically a class of energy-efficient magneto-elastic devices for analogue signal processing. The signals are carried by transverse acoustic waves while the bias magnetic field controls their scattering from a magneto-elastic slab. By tuning the bias field, one can alter the resonant frequency at which the propagating acoustic waves hybridize with the magnetic modes, and thereby control transmission and reflection coefficients of the acoustic waves. The scattering coefficients exhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…M|NM|M phononic spin valves [16] can be calculated by attaching another YIG layer to the free surface of GGG. The transmission and reflection of sound waves in the opposite sandwich, i.e., a thin magnetic film inserted in an infinite nonmagnetic matrix [22], is a simple extension of our model as a function of magnetization angle. Our BCs can also address the energy partition between surface and bulk modes [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M|NM|M phononic spin valves [16] can be calculated by attaching another YIG layer to the free surface of GGG. The transmission and reflection of sound waves in the opposite sandwich, i.e., a thin magnetic film inserted in an infinite nonmagnetic matrix [22], is a simple extension of our model as a function of magnetization angle. Our BCs can also address the energy partition between surface and bulk modes [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…The Landau-Lifshitz-Gilbert (LLG) equation governs the magnetization dynamics and the elastic equation of motion (EOM) that of the underlying lattice. They are coupled by effective forces and fields, which are functional crossderivatives of the total energy [19][20][21][22][23]. This approach is appropriate in the GHz frequency regime in which wavelengths far exceed the lattice constants.…”
Section: Introductionmentioning
confidence: 99%
“…Long-wavelength dipolar spin waves in the magnetic insulator-yttrium iron garnet (YIG)-can even travel over centimeters [6], but they suffer from a low group velocity; exchange spin waves have a large group velocity but their lifetime is shorter [7][8][9][10]. Recent studies showed that bulk phonons in the insulator gadolinium gallium garnet (GGG) can couple two YIG magnetic layers over millimeters [11][12][13][14], raising the possibility of using phonon currents to transfer spin information in nonmagnetic insulators. The surface (Rayleigh) acoustic waves (SAWs), known as excellent sources to pump spin waves via acoustic spin pumping [15][16][17][18][19][20][21], can propagate a longer distance with a larger group velocity [22,23] and thus is promising to transport spin information.…”
Section: Introductionmentioning
confidence: 99%
“…to tilt the resonator's static magnetisation, so as to control the projection of the precession ellipse onto the sagittal plane. One could make use of the propagating mode's angle of incidence 62 and dispersion anisotropy 63,64 to control the orientation of the plane of polarisation of its stray field relative to the resonator's magnetisation. Ultimately, one could use the perpendicular magnetic anisotropy 37,65,66 to control the precession ellipticity directly.…”
Section: B Enhancement and Tuning Of The Chiral Magneto-dipole Couplingmentioning
confidence: 99%